Ecoethical significance of wilderness in Pablo Neruda’s selected poems - Goltaj David Khosravi,; Ravichandran Vengadasamy,; Raihanah M. M., (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper explores the ecoethical vision and ecological awareness in the selected poems of Pablo Neruda, a Nobel Prize winning poet of Latin American descent who was well known as a political poet. The structural and thematic analysis of the study will focus on the concept of ‘Ethics’ as one of the components of ecopoetry, which is the new brand of nature poetry and one of the components of ecocriticism which investigates the human-nature relationship. The objective of this paper is to highlight the significance of ecoethical consideration of Pablo Neruda towards wilderness. The study utilizes the theoretical frameworks of ecocriticism and ecopoetry to illuminate Neruda’s call for reverence of the wilderness, flora and fauna, in the land, the sea and the sky through an ethical consideration of interdependence and interconnectedness of human and nonhuman. This paper problematizes Neruda’s attitude towards nature to obtain new insights into his ethical stand towards the natural world. The discussion focuses on the poems which reflect the sense of ethics and represent the significant role of humility in shaping our sense of accountability towards the wilderness, while revealing Neruda’s ideology and relationship with the non-human world.